Executive Function Skills Are Linked to Restricted and Repetitive Behaviors: Three Correlational Meta Analyses. Issue 6 (6th January 2021) - Iversen, Rebecca Kvisler; Lewis, Charlie
Abstract : There is a consensus on the centrality of restricted and repetitive behaviors (RRBs) in the diagnosis of Autism Spectrum Disorder (ASD), yet the origins of these behaviors are still debated. We reconsider whether executive function (EF) accounts of RRBs should be revisited. EF deficits and high levels of RRBs are often pronounced in individuals with ASD and are also prevalent in young typically developing children. Despite this, the evidence is mixed, and there has been no systematic attempt to evaluate the relationship across studies and between task batteries. We examine recent evidence, and in three highly powered random‐effects analyses ( N  = 2964), examine the strength of the association between RRB levels and performance on set shifting, inhibitory control, and parental‐report based EF batteries. The analyses confirm significant associations between high levels of the behaviors and poor EF skills. Moreover, the associations remained stable across typical development and in individuals with ASD and across different types of EF measures. These meta‐analyses consolidate recent evidence identifying that cognitive mechanisms correlate with high RRBs that are seen in individuals with ASD, as well as in typical development. We propose that the EF account may be critical for guiding future interventions in ASD research. Lay Summary: Restricted and repetitive behaviors (RRBs) are diagnostic criteria for Autism yet also common in typical development, and if they persist over time some can have a negative impact on learning and social acceptance. The present meta‐analyses found that high levels of RRBs related to poor performance on set‐shifting and inhibitory control tasks, as well as high ratings on parental report scales. Future studies should create interventions that aim to improve these skills as they may help manage challenging RRBs.